Absorption coefficients of GeSn extracted from PIN photodetector response - Ye, Kaiheng; Zhang, Wogong; Oehme, Michael; Schmid, Marc; Gollhofer, Martin; Kostecki, Konrad; Widmann, Daniel; Koerner, Roman; Kasper, Erich; Schulze, Jörg (Solid-State Electronics, 2015)
In this paper the optical absorption of the GeSn PIN photodetector was investigated. The vertical GeSn PIN photodetectors were fabricated by molecular beam epitaxy (MBE) and dry etching. By means of current density-voltage (J-V) and capacity-voltage (C-V) measurements the photodetector device was characterized. The absorption coefficients of GeSn material were finally extracted from the optical response of PIN structure. With further direct bandgap analysis the influences of device structure was proved negligible.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Absorption coefficient; Direct bandgap; GeSn; MBE; PIN diode photodetector